Wide-band, passively Q-switched Yb- and Tm-doped fibre laser using WSSe saturable absorber - Ahmad, Harith; Aidit, Siti Nabila; Ooi, Shok Ing; Tiu, Zian Cheak (Taylor & Francis, 2018)
A wide-band, passively Q-switched fibre lasers based on ytterbium- and thulium-doped fibre gain medium are proposed and demonstrated. The lasers employ a transition metal dichalcogenide, tungsten sulphoselenide as a saturable absorber (SA) which is prepared by mechanical exfoliation technique. By integrating the SA in the laser cavities, self-starting Q-switched at 1038 and 1982 nm are obtained. The generated pulses exhibit a microsecond pulse duration with few kilohertz repetition rate. The proposed SA has high potential as a new material to cater to the needs of various scientific, industrial and biomedical applications.